PREDICTING OF FINANCIAL DISTRESS WITH THE ALTMAN Z-SCORE MODEL OF RETAIL COMPANIES LISTED ON IDX - Arohmawati, Putri Puji; Pertiwi, Tri Kartika (Perpustakaan dan Penerbitan Unismuh Makassar, 2021)
This research aims to examine and analyze the impact of current ratio, return on assets, debt to asset ratio, and total asset turnover rate on the estimated financial distress status of retail trading companies listed on the Indonesian stock exchange. This research is a quantitative research. The data used in this study are second hand data. The totality of this research is the retail trade sub-sector companies that were listed on the Indonesian Stock Exchange from 2015 to 2019. The sampling technique is purposeful sampling, with a total of 17 companies. The analysis method used is logistic regression analysis. The results of this research analysis have a significant impact on the variable current ratio, asset return, asset liability ratio and total asset turnover. In part, the current ratio variable has a negative and significant effect, the asset return rate variable has a negative and significant effect, the asset liability ratio variable has a negative and insignificant effect, and the total asset turnover rate variable has a negative and significant effect. Estimate the financial distress status of companies in the retail trading sub-sector listed on the Indonesian Stock Exchange.Keywords: Financial distress, Current Ratio, Return On Assets, Debt to Assets Ratio, Total Assets Turnover